GMBATU anti-privatisation poster, 1985 (1985)
1985 1960-2000 "GMBATU anti-privatisation poster, 1985" [T0591.jpg], 1985 In the mid 1980s, Government plans to extend privatisation into local government and the health service were fiercely opposed by the public service unions. This poster, produced by the General Municipal Boilermakers and Allied Trades Union, condemns the introduction of private contractors into refuse and waste disposal services.